2014
DOI: 10.1186/1471-2458-14-1115
|View full text |Cite
|
Sign up to set email alerts
|

Immigrant women living with HIV in Spain: a qualitative approach to encourage medical follow-up

Abstract: BackgroundImmigrant women living with HIV generally have worse adherence to medical treatment and follow-up when compared to native women and immigrant or native men. The general aim of this study was to improve healthcare services for HIV-positive women and to better understand why some of them discontinue treatment. The specific objectives were: (1) to explore the barriers and facilitators to medical follow-up among women and (2) to use the findings to create a guide for healthcare professionals with strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(55 citation statements)
references
References 22 publications
2
53
0
Order By: Relevance
“…All selected studies included migrants from Southeast Asia and sub-Saharan African countries living in high income countries, specifically those with UHC. Of these 15 studies, seven were conducted in Australia [ 26 , 27 , 28 , 29 , 30 , 31 , 32 ]; two in the UK [ 33 , 34 ] and one study in Sweden [ 35 ], Ireland [ 36 ], Spain [ 37 ], Belgium [ 38 ], and Scotland respectively [ 39 ]. Of the 15 studies, eight studies examined migrants from sub-Saharan African countries [ 29 , 31 , 33 , 34 , 36 , 38 , 39 , 40 ]; two studies examined migrants from Southeast Asia countries [ 26 , 35 ]; and five studies explored migrants from mixed regions [ 27 , 28 , 30 , 32 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…All selected studies included migrants from Southeast Asia and sub-Saharan African countries living in high income countries, specifically those with UHC. Of these 15 studies, seven were conducted in Australia [ 26 , 27 , 28 , 29 , 30 , 31 , 32 ]; two in the UK [ 33 , 34 ] and one study in Sweden [ 35 ], Ireland [ 36 ], Spain [ 37 ], Belgium [ 38 ], and Scotland respectively [ 39 ]. Of the 15 studies, eight studies examined migrants from sub-Saharan African countries [ 29 , 31 , 33 , 34 , 36 , 38 , 39 , 40 ]; two studies examined migrants from Southeast Asia countries [ 26 , 35 ]; and five studies explored migrants from mixed regions [ 27 , 28 , 30 , 32 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Strategies deployed to communicate test results that “cheat users a bit” (E.g. asking an HIV+ user for consent to test for HIV after the test has already been performed) could undermine this crucial factor to effectively promote HIV uptake amongst migrants [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study of the demographic characteristics and mortality of foreign‐born WLWH in the WIHS, we found that most were young and educated, but low income and often unemployed. Age, education, income, employment, social support and access to health services as well as changing HIV treatment guidelines have been highlighted as critical determinants of health and some studies have suggested that these micro and macro factors exert powerful influences on long‐term outcomes and death among foreign born persons[14‐17,27‐29]. Our findings reveal that these demographic characteristics, including access to health insurance and use of ART are all significantly associated with birthplace and are critical to long‐term health outcomes.…”
Section: Discussionmentioning
confidence: 61%
“…Foreign‐born populations, especially women are generally disadvantaged in terms of accessing health care due to a complex set of social and structural factors [5,9‐11], all of which exert powerful negative influences on short‐ and long‐term health outcomes[6,9,12‐17]. Studies suggest that foreign‐born women are more susceptible to the less desirable outcomes of HIV due to low socioeconomic and educational status, language barriers, poor access to health providers, lack of transportation, and lack of documented legal status, among others, and may be negatively impacted in accessing or utilizing services because of similar factors [17,18].…”
Section: Introductionmentioning
confidence: 99%